2022
DOI: 10.1038/s41598-022-24189-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/IL-10 mRNA expression ratio in tumor tissues predicts prognosis in gastric cancer patients without distant metastasis

Abstract: There was growing evidence that inflammatory responses played significant roles in malignancies. However, the impact of pro-inflammatory-to-anti-inflammatory factor ratio in tumor tissues has not been investigated in gastric cancer (GC) yet. We collected patient data from The Cancer Genome Atlas (TCGA) database. A total of 270 stomach adenocarcinoma (STAD) patients without distant metastasis were included in the study. After screening 12 candidate pro-inflammatory-to-anti-inflammatory pairs, only the IL-6/IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Both supplement groups exhibited notable systemic anti-inflammatory effects following a 180-day supplementation period, characterized by a reduction in chemokines closely linked to metabolic and intestinal disorders. Specifically, levels of RANTES 40 , CXCL9/MIG 78 , IL-6, and the IL-6/IL-10 ratio, recognized markers associated with inflammatory diseases such as gastric cancer 79 , witnessed a decrease in both groups. Concurrently, there was an elevation in IL-4 in both supplement groups, renowned for its anti-inflammatory properties 80 .…”
Section: Discussionmentioning
confidence: 99%
“…Both supplement groups exhibited notable systemic anti-inflammatory effects following a 180-day supplementation period, characterized by a reduction in chemokines closely linked to metabolic and intestinal disorders. Specifically, levels of RANTES 40 , CXCL9/MIG 78 , IL-6, and the IL-6/IL-10 ratio, recognized markers associated with inflammatory diseases such as gastric cancer 79 , witnessed a decrease in both groups. Concurrently, there was an elevation in IL-4 in both supplement groups, renowned for its anti-inflammatory properties 80 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that the ratio of IL-6 to IL-10 is strongly correlated with injury severity and the intensity of the anti-inflammatory response after trauma (47). In addition, an imbalance in the systemic inflammatory response, marked by an increased IL-6/IL-10 ratio, is one of the possible factors contributing to the severity of primary open-angle glaucoma (48), gastric cancer (49) or COVID-19 patients (50). Understanding the interplay between IL-6 and IL-10, which reflects the balance between proinflammatory and anti-inflammatory cytokines, is critical for identifying patients in a hyperinflammatory state and will allow rational determination of the best treatment options for each patient (50).…”
Section: Discussionmentioning
confidence: 99%
“…Ранее было показано, что низкая экспрессия ИЛ-10 в опухолевых клетках увеличивает риск неблагоприятного прогноза при раке молочной железы. Cоотносительный уровень мРНК ИЛ-6 / ИЛ-10 намного выше у больных раком желудка с плохим прогнозом, а средний уровень ИЛ-10 в сыворотке крови был статистически значимо ниже у пациентов с колоректальным раком, чем у здоровых лиц, что соответствует полученным нами результатам по экспрессии мРНК ИЛ-10 у больных РПЖ [22][23][24]. Кроме того, сообщается о том, что мыши с дефицитом ИЛ-10 более 3 , n = 34; 3 -group with a PV of more than 50 cm 3 , n = 24; 4 -control group, n = 30; *differences are statistically significant compared with the control group (p <0,01); **differences are statistically significant between the group with a pancreatic volume of up to 25 cm 3 and the group with a pancreatic volume of more than 25 to 50 cm 3 (p <0.05); ***differences are statistically significant between the group with a pancreatic volume of up to 25 cm 3 and the group with a pancreatic volume of more than 50 cm 3…”
Section: результатыunclassified